(untitled) (REMUNOM, 2025)
This study presents the process of reorganizing management and specialized oral health care at the Dental Specialties Center of the Federal University of Pará (CEO-UFPA), located in the Amazon region. In February 2024, the service registered performance below the targets established by the National Oral Health Policy (PNSB), institutionalized by Law No. 14,572/2023, revealing weaknesses in care pathways, limited articulation with Primary Health Care, and constraints in work process governance. In response, a new institutional governance model was implemented, grounded in Brazil’s Unified Health System (SUS) principles and oriented toward the recomposition of the multidisciplinary team, expansion of qualified access, and active integration of dentistry students into managerial, educational, and clinical dimensions of care. The objective of this study was to analyze the organization of care and management processes at CEO-UFPA, based on this institutional transformation experience. This is a descriptive case study with a qualitative approach, supported by 18 months of participant observation, documentary analysis, and monitoring of care indicators in the specialties of stomatology, endodontics, oral surgery, periodontics, operative dentistry, pediatric dentistry, and laser therapy. The results demonstrated advances in resolutive capacity, reduced waiting times, improved clinical records, strengthened relationships with users, and expanded the pedagogical role of the service. As an educational product, the CEO-UFPA Internship Guide was developed, characterized as an educational technology aimed at standardizing workflows, promoting critical training, and fostering health management skills. This experience reinforces the strategic role of public universities in driving sustainable policies that reduce territorial inequities and strengthen the SUS. Its contribution aligns with the United Nations 2030 Agenda Sustainable Development Goals — particularly SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), and SDG 10 (Reduced Inequalities).